EKSEKUSI BARANG JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 - Hanif Nur Kholish (2021)
This study aims to explain the legal discussion regarding the act of withdrawing goods against the authentic deed of fiduciary guarantee against collateral. Requests related to testing regarding the withdrawal of fiduciary collateral that are contradictory to the Constitution of the Republic of Indonesia in this case have the effect of not having binding legal force. So that the creditor must have a court decision before carrying out the execution. In research on the execution of fiduciary collateral, it has binding legal force so that creditors and debtors have rights and obligations in the provisions of the fiduciary guarantee. Taking the action of withdrawing collateral has a variety of security in an incident in the field so that acts are carried out by coercion until the commotion is carried out at a place and time that is not in accordance with the agreement.. Keywords: Guarantee; Execution; Agreement.